95.7k views
2 votes
2x + 3y = -3
x + 2y = 2

User Ajeh
by
5.3k points

2 Answers

6 votes

Answer:

x=-12, y= 7

(-12,7)

Explanation:

use elimination method

2x+3y=-3

x+2y=2

so

-2(x+2y=-3)

-2x-4y=-4

2x+3y=-3

x gets eliminated

-y=-7, -y/-1=-7/-1 = y= 7

plug 7 in one of the equations

x+2(7)=2

x+14=2 subtract 14 by both side

x=-12

to check the answers just plug in -12 in x and 7 in y

-12+2(7)=2

-12+14=2

2=2

User Harshit Kumar
by
6.9k points
6 votes

Answer:

X= -12 Y= 7

Explanation:

User Dylan Glockler
by
6.0k points